STUDY OF THE FEATURES OF THE MUCOUS MEMBRANES OF THE UPPER RESPIRATORY TRACT IN SMOKING STUDENTS OF THE TERMEZ BRANCH OF THE TASHKENT MEDICAL ACADEMY (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The relevance and necessity of conducting a study of the cytomorphological and functional characteristics of the mucous membranes of the upper respiratory tract as a tissue, which is the most important element of the body’s first line of defense against the effects of adverse factors. These tissues accumulate the most (nicotine, pollutants, dust, microorganisms) and have a negative impact on the normal condition of the upper respiratory tract. However, the issue of the damaging effects of cigarette smoke components on the cytogram of the epithelium of the upper respiratory tract and the processes of proliferation and differentiation of its epithelial cells is still controversial and not fully understood.